2008
DOI: 10.3200/jece.39.3.213-227
|View full text |Cite
|
Sign up to set email alerts
|

Class Attendance and Exam Performance: A Randomized Experiment

Abstract: The determination of college students' academic performance is an important issue in higher education. Whether students' attendance at lectures affects students' exam performance has received considerable attention. The authors conduct a randomized experiment to study the average attendance effect for students who choose to attend lectures, which is known in program evaluation literature as the average treatment effect on the treated. This effect has long been neglected by researchers when estimating the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
89
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 19 publications
14
89
2
1
Order By: Relevance
“…Attending classes yields a positive impact on exam performance [1,56,57]. There have been studies done on impact of student non-attendance at lectures on formative assessment tasks and final grades, and relationship between lecture attendance and final exam in various courses [4,30,31].…”
Section: B Impact Of Lecture Attendancementioning
confidence: 99%
“…Attending classes yields a positive impact on exam performance [1,56,57]. There have been studies done on impact of student non-attendance at lectures on formative assessment tasks and final grades, and relationship between lecture attendance and final exam in various courses [4,30,31].…”
Section: B Impact Of Lecture Attendancementioning
confidence: 99%
“…Having a template in the form of pre-released slides could potentially rectify this problem and improve revision techniques. 52 Accessibility of lecture content in the form of online slides, videos and audios have their own contribution to absenteeism. 22 Another study reported that continuous assessment marks were lower in pharmacology students, where students prevention might prevent unwanted consequences of absenteeism on medical student's academic performance.…”
Section: Factors Related To Teaching Material/strategymentioning
confidence: 99%
“…Achalu (2003) identified the use of drugs as the biggest cause of dropout. Given that absenteeism has been associated with poor academic performance (Robert, 2007), Chen & Lin (2008) suggested that attendance to school should be closely monitored, encouraged and enforced. In their own comment Armstrong & Pearson (2008) ;Crede Roch & Kieszczynka (2010) argued that regular attendance to school does not guarantee academic success because many may show up in school without actual participation in learning activities.…”
Section: Introductionmentioning
confidence: 99%